In situ functionalization of wet-spun fibre meshes for bone tissue engineering - Leonor, I. B. (2011)
Bone tissue engineering success strongly depends on our ability to develop new materials combining osteoconductive, osteoinductive and osteogenic properties. Recent studies suggest that biomaterials incorporating silanol (SiOH) groups promote and maintain osteogenesis. The purpose of the present research work was to provide evidence that using wet-spinning technologies and a calcium silicate solution as a coagulation bath, it was possible to develop an in situ functionalization methodology to obtain 3D wet-spun fibre meshes with SiOH groups, through a simple, economic and reliable process. SPCL (blend of starch with polycaprolactone) fibre meshes were produced by wet-spinning, using a calcium silicate solution as a non-solvent and functionalized in situ with SiOH groups. In vitro tests, using goat bone marrow stromal cells (GBMSCs), showed that SPCL–Si scaffolds sustained cell viability and proliferation. Furthermore, high ALP activity and matrix production indicated that SiOH groups improve cellular functionality towards the osteoblastic phenotype. Using this methodology, and assembling several wet-spun fibre meshes, 3D meshes can be developed, aiming at designing osteoconductive/osteoinductive 3D structures capable of stimulating bone ingrowth in vivo.